Parboiled rice processing method, rice quality, health benefits, environment and future perspectives: a review - Muchlisyiyah, Jhauharotul; Shamsudin, Rosnah; Kadir Basha, Roseliza; Shukri, Radhiah; How, Syahmeer; Niranjan, Keshavan; Onwude, Daniel (Multidisciplinary Digital Publishing Institute, 2023)
Parboiled rice is recognized for its greater milling yield and reduced rice breakage compared to raw rice during processing. Additionally, parboiled rice has better glycemic control and numerous health benefits. However, the production of parboiled rice requires energy-intensive processing as well as wastewater production. This study reviews parboiled rice, including its processing condition, nutritional properties, potential use, emerging green technologies, and health benefits. It also discussed the outlook and challenges regarding parboiled rice. In addition, a novel overview of emerging green solutions applied to the process to minimize wastewater creation during parboiling and reduce excessive energy usage is provided. The limitation of parboiled rice for a new market preference is the color. An intense process would cause an unwanted physical appearance. A thorough study should balance the multiple advantages of parboiled rice with the reasonable intensity of the process. Due to its multiple advantages, parboiled rice is demonstrated to be a possible breakthrough in the agriculture and food industries. This review aims to provide a thorough understanding that can be used for academic and industrial purposes.